2020
DOI: 10.1155/2020/4964202
|View full text |Cite
|
Sign up to set email alerts
|

GPA Peptide-Induced Nur77 Localization at Mitochondria Inhibits Inflammation and Oxidative Stress through Activating Autophagy in the Intestine

Abstract: Inflammatory bowel disease (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), is a chronic inflammatory disease affecting the colon, and its incidence is rising worldwide. Nur77, belongs to the NR4A subfamily of nuclear hormone receptors, plays a critical role in controlling the pathology of colitis. The aim of this study is to investigate the protection effect and mechanism of Gly-Pro-Ala (GPA) peptide, isolated from fish skin gelatin hydrolysate, in a mouse model of dextran sulfate sodium- (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 66 publications
(88 reference statements)
0
8
0
Order By: Relevance
“…It has been reported that oxidative stress and inflammatory signals concurrently play roles that negatively impact adipose tissue and disrupt the regulation of vascular function in obesity [ 62 ]. Research has also revealed that body fluctuations resulting from metabolic disorders contribute to alterations in the gut microbial bacteria balance and disruption of the intestinal epithelial barrier which may trigger the release of pro-inflammatory cytokines and reactive oxygen species [ 63 ]. This process eventually leads to a cycle of uncontrolled oxidative stress and inflammation in the body [ 63 ].…”
Section: Gut Microbiota Obesity and Hydrolysates/bioactive Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that oxidative stress and inflammatory signals concurrently play roles that negatively impact adipose tissue and disrupt the regulation of vascular function in obesity [ 62 ]. Research has also revealed that body fluctuations resulting from metabolic disorders contribute to alterations in the gut microbial bacteria balance and disruption of the intestinal epithelial barrier which may trigger the release of pro-inflammatory cytokines and reactive oxygen species [ 63 ]. This process eventually leads to a cycle of uncontrolled oxidative stress and inflammation in the body [ 63 ].…”
Section: Gut Microbiota Obesity and Hydrolysates/bioactive Peptidesmentioning
confidence: 99%
“…Research has also revealed that body fluctuations resulting from metabolic disorders contribute to alterations in the gut microbial bacteria balance and disruption of the intestinal epithelial barrier which may trigger the release of pro-inflammatory cytokines and reactive oxygen species [ 63 ]. This process eventually leads to a cycle of uncontrolled oxidative stress and inflammation in the body [ 63 ]. Thus, activities that reduce chances of developing metabolic disorders, such as weight management can act as appropriate therapeutic approaches to prevent excessive oxidation and inflammatory signaling in the body.…”
Section: Gut Microbiota Obesity and Hydrolysates/bioactive Peptidesmentioning
confidence: 99%
“…The expression of METTL3 was determined in collected clinical IBD and normal control colon samples, as well as in the DSS-induced IBD mouse model. Mouse intestinal epithelial cells are widely used as in vitro models for IBD-related research [ 18 , 19 ]. lipopolysaccharides (LPS) were known to be increased in IBD mucosa [ 20 ] and also use to mimic the inflammatory response in IBD [ 18 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mouse intestinal epithelial cells are widely used as in vitro models for IBD-related research [ 18 , 19 ]. lipopolysaccharides (LPS) were known to be increased in IBD mucosa [ 20 ] and also use to mimic the inflammatory response in IBD [ 18 , 21 ]. Herein, we transfected a mouse intestinal epithelial cell line MODE-K with lentivirus contained short hairpin RNA targeting METTL3 to achieve METTL3 knockdown, treated the cell line with LPS, and determined cell viability, apoptosis, apoptotic caspase3/9, inflammatory factor (IL-1β, TNF-α, IL-6, and IL-18) and inflammatory enzymes (COX-2 iNOS).…”
Section: Introductionmentioning
confidence: 99%
“…After 14 days, the mice were humanely euthanized, and the colons were excised, measured, and sectioned for further analysis. [26][27][28] Subsequently, to further confirm the key role of Nur77 in the effect of GPA, GPA was intragastrically administered daily at 100 mg/kg. Wild-type (WT) or Nur77 −/− mice were randomly assigned to the control group, DSS group, and GPA (100 mg/kg) + DSS group.…”
Section: Establishment Of Dss-induced Mice Colitis Model and Treatmentmentioning
confidence: 99%